2011
DOI: 10.3892/or.2010.1107
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA acts via p38 MAPK to induce apoptosis and the down-regulation of ERCC1 and lung-resistance protein in cisplatin-resistant ovarian cancer cells

Abstract: Abstract. Tanshinone IIA is known to induce apoptosis in several types of cancer cells. However, little is known about its activity in chemoresistant cells. The aim of this study was to investigate the anticancer properties of tanshinone IIA in cisplatin-resistant human ovarian cancer COC1/DDP cells in vitro. We used a variety of methods to measure cell viability, the resistance index (RI) of cisplatin, cellular apoptosis, p38 mitogen-activated protein kinase (MAPK) expression and phosphorylation, and the mRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…These studies indicate that survivin is involved in multiple biological processes in EOC. Previous studies have shown that p38 MAPK is required for survivin downregulation in Tanshinone IIA and a high dose of nitric oxide-induced apoptosis in established EOC cell lines [21,35,36]. Our results show that inhibition of p38 MAPK by SB203580 increases survivin protein level in the primary EOC cells, which is consistent with the published results in established EOC cell lines [21,35,36].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…These studies indicate that survivin is involved in multiple biological processes in EOC. Previous studies have shown that p38 MAPK is required for survivin downregulation in Tanshinone IIA and a high dose of nitric oxide-induced apoptosis in established EOC cell lines [21,35,36]. Our results show that inhibition of p38 MAPK by SB203580 increases survivin protein level in the primary EOC cells, which is consistent with the published results in established EOC cell lines [21,35,36].…”
Section: Discussionsupporting
confidence: 92%
“…Survivin is implicated in cisplatin-induced cytotoxicity in EOC [33,34]. Because published studies showed that p38 MAPK mediates survivin downregulation and apoptosis induced by tanshinone IIA and a high dose of nitric oxide in EOC cells [21,35,36], we examined how carboplatin and SB203580 treatment affects survivin expression in the primary EOC cells. Western blotting showed that SB203580 increased the expression of survivin in all primary EOC cells compared to the DMSO control, albeit to a variable extent (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations